"His lectures were like watching a show on Netflix": A success story of laugh tracks in prerecorded undergraduate lessons. Issue 2 (15th December 2022) - Varhola, Andrés
Abstract: The onset of the COVID‐19 pandemic in 2020 put enormous pressure on educators to quickly adapt course materials for online delivery. In my case, a naturally humorous teaching style clashed with the arid world of computers in a virtual environment, leading me to believe in a reduced teaching effectiveness under such conditions, and that my students would suffer from countless hours of dull screentime. This article narrates the story of how a simple technique—adding laugh tracks to prerecorded videos in forestry undergraduate courses—was the foundation of a comprehensive approach to design online instruction with a high entertainment value. Several ideas to integrate humor in online (and face‐to‐face) learning are described based on these experiences and are accompanied by a brief theoretical background highlighting the value of bringing laughter to academic settings. Student feedback clearly indicated that the use of laugh tracks and other humorous elements was well received, especially during the challenging times of learning under lockdowns. Core Ideas: Creating online courses in light of COVID was hard because of disparities between teaching styles and virtual setting. My humorous style was impeded at the beginning of online course delivery, threatening my enjoyment as an educator. I delivered courses via prerecorded videos with jokes as in‐person and laugh tracks to replace a live audience. The technique was well received, leading to more ideas for incorporating humor in course design and delivery. Student feedback strongly indicated that humor enhanced the learning experience during such tough times.